Current evidence for thoracic aorta type B dissection management. (December 2014) - Capoccia, Laura; Riambau, Vicente
Aortic dissection is a devastating cardiovascular condition and represents the most common aortic emergency. Outcome is determined by the type and extent of dissection and the presence of associated complications requiring early diagnosis and treatment. Aortic dissection is defined as acute within 14 days from onset and chronic after that time period. The natural course of type B dissection is determined by 2 elements, early and chronic complications. An uncomplicated acute type B dissection is less frequently lethal but it is not totally benign. Some peculiar issues must be taken into account, such as the high probability of complications development in a dissected aorta and the poor long-term prognosis on medical treatment alone. Then, it would be helpful to identify which patients with uncomplicated type B dissection will have a poorest aortic prognosis over time in order to apply an early intervention.